Roman and Byzantine Motifs in Сказаниe о князьях владимирских (The Tale of the Princes of Vladimir) - Dana Picková (Acta Universitatis Carolinae: Philologica, 2017)
Vasily III and to a greater extent Ivan the Terrible based their policies on a historical work known as Сказание о князьях владимирских (The Tale of the Princes of Vladimir). Its author attempted to find a connection between the House of Rurikids and the Byzantine and the ancient Roman Empire, although in a completely different context than monk Philotheus of Pskov who invented the idea of eternal Moscow as the third Rome. According to the concept of the author of Сказание, Rurik was a descendant of Prus, a relative of Roman Emperor Octavianus Augustus while Vladimir II Monomakh was said to obtain the insignia of imperial power from the Byzantine Emperor Constantine IX Monomakhos.